TENSES IN WRITING AN ENGLISH ABSTRACT - Fiqih Kartika Murti (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2022)
Some people say that writing an English abstract is difficult because they have to pay attention to the use of English grammar. Moreover, writing an English abstract has to use correct tenses. Each component of the abstract should use different tenses. The study aimed to describe the tenses used in the English abstract of the articles published in the online journal of Universitas Bhamada Slawi and analyze the errors in tense. The study was qualitative research with a descriptive method. The population was 221 documents; those were checked by inclusion and exclusion criteria resulting in 101 abstracts from the two journals. The obtained data were analyzed by data triangulation. Based on the data analysis, it described two types the use of tenses in the English abstract; simple present tense for all (57 abstracts) and a combination of simple present and past tense (44 abstracts). Also, there were some sentences categorized by errors in tenses. In conclusion, two tenses are used to arrange an English abstract; simple present tense for "background" and "conclusion", and past tense for arranging "purpose", "method", and "result". To avoid more errors in tenses, the journal should enclose a file including the use of exact tenses in each part of the abstract.